How do corporate taxes affect international trade? - Mario Holzner; Branimir Jovanović; Goran Vukšić (The Vienna Institute for International Economic Studies (wiiw), 2021)
This paper investigates how corporate income taxes affect international trade, and identifies the underlying channel. Using data on 33 NACE sectors, for 34 EU and OECD economies, over the period 2005-2014, we find that corporate income taxes reduce exports and imports only when the stock of foreign direct investment (FDI) is high. The effect is present primarily in the service sector and in countries with low corporate taxes. We interpret these findings as evidence that multinational enterprises reduce their operations in countries that raise their corporate taxes. The effect has been found to be small on aggregate, implying that the expected increase in corporate taxes in the future, arising from the global minimum tax, is unlikely to hurt international trade.
Keywords: F14; F23; H25; 330; taxation; profits; international trade; exports; imports; FDI